The Functions of PRDM3 in Different Cell Behaviors - Li, Xin (Journal of Student Research, 2024)
PRDM3 is a unique protein with an N-terminal PR domain and zinc finger motifs in the PRDM family and is very important in acute leukemia. PRDM3 has a special structural function with the particular PR domain that plays an essential role in acute leukemia and hematopoiesis. PRDM3 has unique mechanisms for different cell behaviors, including apoptosis, cell differentiation, and proliferation. These mechanisms are associated with leukemias. PRDM3 is also a protein that may have an enzyme function to modify chromatin and govern gene expression. Finally, these functions of PRDM3 in different cell behaviors showed that PRDM3 is a promising therapeutic target for leukemia.